Clinical, diagnostic and therapeutic aspects of feline asthma: Literature review (Research, Society and Development, 2024)
Feline asthma is an inflammatory disease affecting the caudal respiratory tract of cats, the species being the only one that presents a syndrome similar to that of humans. Its pathophysiology is not fully understood, but it is known that an exacerbated response to exposure to aeroallergens occurs. Affected animals tend to be young and middle-aged, with no predilection for breed or sex, although studies indicate that there is a greater predisposition in Siamese. Clinically, it can manifest itself as coughing, dyspnea, sneezing, exercise intolerance, tachypnea, expiratory wheezing and/or noisy breathing, making its diagnosis challenging, including history, clinical signs, physical examination findings and association with diagnostic tests, such as bronchoscopy, microbiological and cytological analysis of bronchoalveolar lavage, imaging tests, pulmonary function testing and laboratory tests. Treatment is based on the administration of bronchodilators, corticosteroids and environmental management, aiming to reduce exposure to allergens. The objective of the present study is to carry out a literature review on feline asthma, in order to address, above all, the clinical, diagnostic and therapeutic aspects of the disease. A narrative literature review was carried out with research based on data from the PUBMED, Scielo and Google academic platforms, in addition to the use of veterinary medicine textbooks.